The debate over 'Thirlwall's law': balance-of-payments-constrained growth reconsidered - Robert A. Blecker (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
Several recent critiques have questioned the theoretical logic of standard models of balance-of-payments-constrained growth (BPCG) and the empirical support for 'Thirlwall's law'. On the empirical side, critics charge that most econometric estimates of this model have effectively only tested whether exports and imports grow at similar rates in the long run. On the theoretical side, the criticisms have focused on the role of foreign income growth, capital accumulation, relative prices and country size in BPCG models. This article reviews the current state of the debate over these critiques and also offers a brief discussion and evaluation of three alternative models. The alternative models all highlight a significant role for the level of relative prices (or the real exchange rate) in determining long-run growth, which is consistent with recent empirical studies.
Keywords: E12; F43; F32; O41; 330; balance-of-payments-constrained growth; Thirlwall's law; relative prices; real exchange rates